Juan Ortiz Escamilla y José Antonio Serrano Ortega (eds.), Ayuntamientos y liberalismo gaditano en México, México, El Colegio de Michoacán-Universidad Veracruzana, 2007, 503 pp. - Tío Vallejo, Gabriela (Boletín del Instituto de Historia Argentina y Americana Dr. Emilio Ravignani, 2009)